2016
DOI: 10.1186/s13006-016-0085-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of non-exclusive breastfeeding of infants during the first six months in rural area of Sorro District, Southern Ethiopia: a cross-sectional study

Abstract: BackgroundDespite the importance of exclusive breastfeeding, a wide number of mothers practice non-exclusive breastfeeding in Ethiopia. Therefore, this study aimed to identify prevalence and factors associated with non-exclusive breastfeeding in rural area of Sorro District in Southern Ethiopia.MethodsA community based cross-sectional study was undertaken. The study population consisted of all mothers with infants aged of 0–5 months living in the randomly selected kebeles (lowest administrative unit) in the ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
41
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 18 publications
10
41
2
3
Order By: Relevance
“…Mothers who had at least one ANC visit had 2.24 times significantly higher chance of exclusively breastfeed compared with mothers who had no ANC visit. Egger's regression test for funnel plot asymmetry was not significant (z = 1.69, p = 0.09) (Supplementary Furthermore, seven studies 40,42,47,50,51,53,57 reported the association between EBF and PNC in 2,995 mothers (Table 2C). The pooled OR of PNC was 1.86 (95% CI 1.41 -2.47, p <0.0001, I 2 = 63.4%) ( figure 6).…”
Section: Ebfmentioning
confidence: 97%
See 2 more Smart Citations
“…Mothers who had at least one ANC visit had 2.24 times significantly higher chance of exclusively breastfeed compared with mothers who had no ANC visit. Egger's regression test for funnel plot asymmetry was not significant (z = 1.69, p = 0.09) (Supplementary Furthermore, seven studies 40,42,47,50,51,53,57 reported the association between EBF and PNC in 2,995 mothers (Table 2C). The pooled OR of PNC was 1.86 (95% CI 1.41 -2.47, p <0.0001, I 2 = 63.4%) ( figure 6).…”
Section: Ebfmentioning
confidence: 97%
“…Egger's regression test for funnel plot asymmetry was not significant (z = 1.64, p = 0.10). Furthermore, 7 studies 36,38,43,46,47,49,52 reported the association between EBF and PNC in 2,995 mothers (Table 2C). The pooled OR of PNC was 1.86 (95% CI 1.41 2.47) ( figure 6).…”
Section: Exclusive Breastfeedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Egger's regression test for funnel plot asymmetry was not significant (z = -0.99, p = 0.32). In addition, ten (51,65,66,(69)(70)(71)(72)(73)(74)(75) out of 23 studies reported the association between EBF and infant age with a total sample of 6,763 mothers. The pooled OR of infant age was 1.86 (95% CI 1.45 -2.39, p <0.001) ( figure 5).…”
Section: Exclusive Breastfeedingmentioning
confidence: 99%
“…Egger's regression test for funnel plot asymmetry was not significant (z = 2.31, p = 0.02). Finally, 12 studies (50,53,64,68,(71)(72)(73)(74)(75)(76)(77)(78) reported the association between EBF and colostrum discarding with a sample of 6,035 mothers. As indicated in figure 6, the pooled OR of colostrum discarding was 0.56 (95% CI 0.37 -0.84, p = 0.005).…”
Section: Exclusive Breastfeedingmentioning
confidence: 99%